Analisis Peran Stakeholder Terhadap Konsep Community Based Tourism (CBT) Di Desa Wisata Kubu Gadang Kota Padang Panjang - Dianni Oktaria Putri; Harry Yulianda; Emiliyani Wahyuni; Febria Rahim (i-Tourism: Jurnal Pariwisata Syariah, 2025)
Kubu Gadang Tourism Village is one of the tourism villages that has developed the concept of Community-Based Tourism (CBT) with the involvement of the local community in the development of the tourism village. However, despite having a well-established development concept, the role of stakeholders has not yet had a significant impact. This study aims to analyze the role of stakeholders in the development of Community-Based Tourism (CBT) in Kubu Gadang Tourism Village, Padang Panjang City, the winner of the Indonesian Tourism Village Award (ADWI) 2023 in the Advanced Tourism Village category. This study employs a descriptive qualitative approach through observation, in-depth interviews with stakeholders, and documentation from various sources. Data analysis is conducted according to Sugiono (2016), which includes data reduction, data presentation, and drawing conclusions. The research findings indicate that primary stakeholders play an active role in managing tourist attractions, providing homestays, promoting MSME products, and organizing local cultural activities such as silek lanyah and makan bajamba. Meanwhile, secondary stakeholders provide support in the form of infrastructure development, training, and promotion of tourist villages. However, following the victory of ADWI 2023, there has been a decline in the number of tourist visits, indicating the need for an evaluation of the sustainability of stakeholder roles. This study also highlights the importance of integrating Sharia principles into the development of community-based tourism villages, given the socio-cultural characteristics of the Minangkabau community, which are rooted in the philosophy of Adat Basandi Syara', Syara' Basandi Kitabullah (ABS-SBK). Therefore, the active and collaborative involvement of all stakeholders must be enhanced to ensure that the development of CBT in Kubu Gadang Tourism Village is sustainable, inclusive, and aligned with Islamic values.